Patterns of food and physical activity environments related to children's food and activity behaviors: A latent class analysis. (January 2018) - DeWeese, Robin S.; Ohri-Vachaspati, Punam; Adams, Marc A.; Kurka, Jonathan; Han, Seung Yong; Todd, Michael; Yedidia, Michael J.
Abstract: Relationships between food and physical activity (PA) environments and children's related behaviors are complex. Latent class analyses derived patterns from proximity to healthy and unhealthy food outlets, PA facilities and parks, and counts of residential dwellings and intersections. Regression analyses examined whether derived classes were related to food consumption, PA, and overweight among 404 low-income children. Compared to children living in Low PA-Low Food environments, children in High Intersection&Parks-Moderate Density&Food, and High Density-Low Parks-High Food environments, had significantly greater sugar-sweetened beverage consumption (ps<0.01) and overweight/obesity (ps<0.001). Children in the High Density-Low Parks-High Food environments were more likely to walk to destinations (p = 0.01) Recognizing and leveraging beneficial aspects of neighborhood patterns may be more effective at positively influencing children's eating and PA behaviors compared to isolating individual aspects of the built environment. Highlights: Food and physical activity behaviors are influenced by environmental patterns. Children in dense urban neighborhoods may walk more and eat more unhealthy foods. Improved food environments can benefit children who walk for transportation.